Quantifying Non‐Thermal Silicate Weathering Using Ge/Si and Si Isotopes in Rivers Draining the Yellowstone Plateau Volcanic Field, USA. (8th November 2021) - Gaspard, François; Opfergelt, Sophie; Hirst, Catherine; Hurwitz, Shaul; McCleskey, R. Blaine; Zahajská, Petra; Conley, Daniel J.; Delmelle, Pierre
Abstract: In active volcanic regions, high‐temperature chemical reactions in the hydrothermal system consume CO2 sourced from magma or from the deep crust, whereas reactions with silicates at shallow depths mainly consume atmospheric CO2 . Numerous studies have quantified the load of dissolved solids in rivers that drain volcanic regions to determine chemical weathering rates and atmospheric CO2 consumption rates. However, the balance between thermal and non‐thermal components to riverine fluxes in these areas remains poorly constrained, hindering accurate estimates of atmospheric CO2 consumption rates. Here we use the Ge/Si ratio and the stable silicon isotopes (δ 30 Si) as tracers for quantifying non‐thermal silicon contributions in rivers draining the Yellowstone Plateau Volcanic Field, USA. The Ge/Si ratio (µmol.mol −1 ) was determined for seven thermal water samples (183 ± 22), eight rivers (35 ± 23) and six creeks flowing into Yellowstone Lake (5 ± 3) during base flow and during peak water discharge following snowmelt. The δ 30 Si value (‰) was determined for thermal waters (−0.09 ± 0.04), Yellowstone River at Yellowstone Lake outlet (1.91 ± 0.23) and creek samples (0.82 ± 0.29). The calculated atmospheric CO2 consumption associated with non‐thermal waters flowing through Yellowstone's rivers during peak discharge is ∼3.03 ton.km −2 .yr −1, which is ∼2% of the annual mean atmospheric CO2 consumption in other volcanic regions. This study highlights the significance of quantifying seasonal variations in chemical weathering rates for improving estimates of atmospheric CO2 consumption rates in active volcanic regions. Plain Language Summary: The rates of chemical reactions between Earth's rocks and atmospheric CO2 have a major control on global climate over geological time scales. To quantify how much atmospheric CO2 is consumed by the chemical reactions between rocks and atmospheric CO2, many studies have measured the flux of elements derived from these reactions in rivers that drain large watersheds. However, in rivers that drain active volcanic areas, many of the elements are derived from high‐temperature reactions at depth between rocks and CO2 from a deep source, and not from reactions with atmospheric CO2 . The balance between elements sourced from depth and those derived from near‐surface reactions with atmospheric CO2 varies seasonally. In this study, we quantify the balance between these two sources in rivers that drain the Yellowstone Plateau Volcanic Field, USA. We use the germanium to silicon ratio and the stable isotopes of silicon as tracers to quantify the time‐dependent balance. Results from this study highlight the significance of accounting for seasonal changes in the balance between thermal and non‐thermal sources of elements flowing in rivers. Accounting for these variations can improve estimates of atmospheric CO2 consumption rates, and ultimately improve the understanding of variations in the global climate. Key Points: The Ge/Si ratio and Si isotope compositions in thermal waters from Yellowstone Caldera reflect high temperature water‐rhyolite reactions Seasonal variations in riverine Ge/Si and Si isotope compositions reflect a changing balance between thermal and non‐thermal waters Seasonal stream chemistry data across flow regimes are needed to quantify weathering rates and commensurate CO2 consumption